2008
DOI: 10.1099/jmm.0.2008/002642-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of emm type and antibiotic susceptibility of group A streptococci causing invasive and noninvasive disease

Abstract: To determine the prevalence of macrolide antibiotic and levofloxacin resistance in infections with Streptococcus pyogenes (group A streptococcus or GAS), strains were collected from 45 medical institutions in various parts of Japan between October 2003 and September 2006. Four hundred and eighty-two strains from patients with GAS infections were characterized genetically. Strains were classified into four groups according to the type of infection: invasive infections (n574) including sepsis, cellulitis and tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 20 publications
(20 reference statements)
3
36
0
Order By: Relevance
“…ML and levofloxacin resistance rates of S. dysgalactiae subsp. equisimilis were the same as for GAS (Wajima et al, 2008), but different from those reported for GBS in Japan (Murayama et al, 2009). …”
Section: Susceptibility To 12 Agentsmentioning
confidence: 64%
See 3 more Smart Citations
“…ML and levofloxacin resistance rates of S. dysgalactiae subsp. equisimilis were the same as for GAS (Wajima et al, 2008), but different from those reported for GBS in Japan (Murayama et al, 2009). …”
Section: Susceptibility To 12 Agentsmentioning
confidence: 64%
“…Three ML resistance genes, erm(A) (Seppälä et al, 1998), erm(B) (Trieu-Cuot et al, 1990) and mef(A) (Clancy et al, 1996;Tait-Kamradt et al, 1997), were identified by PCR, as described previously (Wajima et al, 2008). Isolates with the erm(A) gene show an inducible ML/lincosamide/streptogramin B resistance phenotype, whilst strains with the erm(B) gene show a constitutive ML/ lincosamide/streptogramin B resistance phenotype arising from methylation of 23S rRNA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Macrolide resistance has gradually increased in S. pyogenes isolates around the world, including Japan (Wajima et al 2008;Arai et al 2011). Resistance of S. pyogenes to macrolides is mainly caused by two mechanisms: one involving 23S ribosomal RNA methylase genes (ermB and ermA) and the other involving the efflux determinant mefA (Sutcliffe et al 1996;Seppala et al 1998).…”
Section: Discussionmentioning
confidence: 99%